Pengembangan Media Pembelajaran Fisika Berbasis Videoscribe Pada Materi Momentum dan Impuls Untuk Meningkatkan Berpikir Kritis Peserta Didik - Doyan, Aris; Listari, Ayu; Ayub, Syahrial (Kappa Journal, 2023)
Learning media is a container for messages that educators want to convey to students, which aims to achieve an effective and efficient learning process. Along with the development of learning media technology, it is necessary to continue to develop so that the quality of education can get better. One of the media that can be used in learning is videoscribe. This study aims to determine the feasibility, practicality and effectiveness of videoscribe-based physics learning media that have been developed to improve students' critical thinking. This study uses the Research and Development (R&D) research method with a development model consisting of define, design, develop, and disseminate stages. Feasibility was reviewed by 6 validators consisting of 3 expert validators and 3 practitioner validators. Practicality is seen from the results of student responses and the implementation of learning. Effectiveness is seen from the results of the trial limited to 1 class at SMAN 1 Alas Barat. The research instruments consisted of videographs, validation sheets, student response questionnaires, and observation sheets of learning implementation and concept understanding tests. Data analysis techniques consist of quantitative descriptive and N-gain test. The results of the study show that learning media is feasible to use with an average of 3.4 with very good categories and research reliability reaches > 75% with reliable criteria. This research is also effective because there is an increase in students' critical thinking with an average N-gain score of 60.24 with moderate criteria. The conclusion is that videoscribe-based physics learning media is feasible, practical, and effective for increasing students' critical thinking theory of momentum and impulse